1994
DOI: 10.1007/bf00014591
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of photosynthesis to increasing atmospheric CO2: The gas exchange perspective

Abstract: The nature of photosynthetic acclimation to elevated CO2 is evaluated from the results of over 40 studies focusing on the effect of long-term CO2 enrichment on the short-term response of photosynthesis to intercellular CO2 (the A/Ci response). The effect of CO2 enrichment on the A/Ci response was dependent on growth conditions, with plants grown in small pots (< 5 L) or low nutrients usually exhibiting a reduction of A at a given Ci, while plants grown without nutrient deficiency in large pots or in the field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
506
5
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 592 publications
(551 citation statements)
references
References 88 publications
27
506
5
13
Order By: Relevance
“…C 4 plants, in contrast to C 3 plants, are reported to be better adapted to water stress [10,11] due to its (i) distinctive leaf anatomy (Kranz anatomy) (ii) having two carboxylation pathways (phosphoenolpyruvate carboxylase (PEPC) and RUBISCO) in mesophyll and bundle sheats that limit photorespiration and increase carboxylation efficiency [12] and (iii) requiring a lower CO 2 saturation point for photosynthesis than C 3 plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…C 4 plants, in contrast to C 3 plants, are reported to be better adapted to water stress [10,11] due to its (i) distinctive leaf anatomy (Kranz anatomy) (ii) having two carboxylation pathways (phosphoenolpyruvate carboxylase (PEPC) and RUBISCO) in mesophyll and bundle sheats that limit photorespiration and increase carboxylation efficiency [12] and (iii) requiring a lower CO 2 saturation point for photosynthesis than C 3 plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al (1998) also reported that short term exposure of elevated CO 2 for plants generally leads to increased rates of leaf-level photosynthesis due to enhanced activity of RuBisCO. On the other hand, photosynthesis down regulation is characterized at the biochemical and leaf levels by reduced chlorophyll content, reduced RuBisCO content and activity and decreased leaf nitrogen concentration on a leaf mass basis (Sage 1994, Tissue et al 1995. It warrants further research to understand the reason for higher leaf N in some species and lower N levels in leaf in other species when plants are exposed to elevated CO 2 .…”
Section: Clonesmentioning
confidence: 99%
“…To use nitrogen efficiently, nitrogen should be reallocated from non-limiting to limiting processes (Evans 1989;Hikosaka and Terashima 1995). It has been suggested that nitrogen reallocation from RuBP carboxylation to the RuBP regeneration processes would increase photosynthetic nitrogen use efficiency at elevated CO 2 (Sage 1994;Webber et al 1994;Medlyn 1996). Using a theoretical model of nitrogen partitioning in the photosynthetic apparatus, Hikosaka and Hirose (1998) suggested that nitrogen reallocation to RuBP regeneration in the doubled CO 2 level would increase photosynthesis by 20%.…”
Section: Leafmentioning
confidence: 99%
“…It is still increasing at a rate of 1.5 lmol mol À1 per year and may reach 700 lmol mol À1 at the end of this century (IPCC 2001). Because CO 2 is a substrate for photosynthesis, an increase in atmospheric CO 2 concentration stimulates photosynthetic rates in C 3 plants (Kimball 1983;Cure and Acock 1986;Bazzaz 1990;Poorter 1993;Sage 1994;Curtis 1996;Ward and Strain 1999). However, the effect of elevated CO 2 on growth and reproduction is often much weaker than that predicted by the photosynthetic response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation